(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Risk assessment has become the cornerstone of contemporary auditing practice, fundamentally transforming how audits are planned, executed, and evaluated. This study examines the theoretical foundations, practical applications, and effectiveness of risk-based auditing approaches in financial statement audits. Through analysis of professional standards, empirical research, and case studies, this article explores how auditors identify, assess, and respond to various categories of risk including inherent risk, control risk, and detection risk. Findings indicate that risk-based approaches significantly enhance audit efficiency and effectiveness when properly implemented, though challenges persist in risk assessment accuracy, professional skepticism application, and adaptation to emerging risks. The study concludes that while risk-based auditing represents best practice, ongoing professional development, technological integration, and methodological refinement remain essential for addressing increasingly complex business environments.